Do silêncio à fala : o caminho da mensagem jornalística - Lage, Louise Costa (1998)
How a corrent of opinion succeeds to break the blockage imposed on it and becomes a reference for the construction of a new paradigm? How the hegemony of a ideology is borken? How an ideological paradigm overcomes its reverse and what role has de press in this change that hits thg believes and the imagin􀀞ry of a whole Nation? This study aims to describe the process by which an occurrence leaves íts latent and silent condition and enters_ the daily discussions of the population. lt is our goal to. try to highlight the elements that give rise to the rupture between silence and speech and also to demonstrate how this process is built in public opinion, aíded by the press. Using the methodological assumptions of the theories of Silent Spiral, Agenda -Setting and Spheres of Controversy, we propose a contextual and discoursive analyses of the privatization process in Brazil, between the 70 and 90 decades. We took as a corpus of analysis the joumalistic coverage realized by the newspaper Folha de São Paulo, the public opinion researches conceming this subject and strategic speaches made by well-konown politicians at tbat time.